Urban policies in the framework of the 2030 Agenda: the case of Bristol, England - Carpenter, J; Valler, D (Springer, 2023)
The UK case study in Bristol provides an example of how a local authority, in partnership with an engaged university, other local stakeholders and a strong civil society, can harness a global agenda that has been sidelined by national government. The Sustainable Development Goals (SDGs) went from being largely unknown in UK local government circles to being a core part of Bristol’s ‘One City Plan’ and the city’s Covid recovery strategy over a period of two years. The critical role of the SDGs in prompting dialogue and bringing together stakeholders with different priorities, particularly the tensions between the ‘green’ and ‘inclusion’ agendas, is highlighted. Several lessons emerge, including the importance of multi-stakeholder engagement, promoting the SDG ethos within communities and strong communications. Awareness and understanding of the SDGs are relatively low, and a strong communication strategy that maps the SDGs onto local issues and challenges can increase their comprehension and influence. Although Bristol's experience shows what can be achieved in a short period, much is still to be done to meet the UN's Agenda 2030 targets. Stable, well-resourced budgetary environments are necessary, including resources for community initiatives and partnership coordinators to bring stakeholders together. A strong focus on trade-offs and prioritisation can help resolve the complex and conflicting issues raised by the SDGs. Many cities across the UK would benefit from support to mirror Bristol's structures, particularly for the Voluntary Local Review. Resources to support collaboration between cities would ensure that lessons learned from Bristol's experience could be applied elsewhere to support local action on global challenges.